Curriculum Autonomy for Bhutanese Schools : A Fitting Solution to the Current Crisis in Bhutanese Education System - Tenzin Dorji (Papanda Publishier, 2023)
This paper aims to address the current crisis in Bhutan's education system by proposing a shift towards providing curriculum autonomy to schools. Drawing on George S. Counts' theory of 'Dare the School Build a New Social Order,' it discusses the limitations of the centralized curriculum system and its impact on Bhutanese education. By examining issues such as the centralized textbook distribution, the propagation of 'Diploma Disease,' and the need for decentralization, the paper argues for delinking schools from the central curriculum and empowering them with more autonomy. This shift is seen as essential to promote relevant education, provide better opportunities, and enhance the overall education quality.